Study on Embryo Transfer System for Production of Transgenic Pigs - Seungwon Na; Euncheol Lee; Ghangyong Kim; Kyuhong Min; Youngkwang Yu; Pantu Kumar Roy; Xun Fang; Bahia Mohamed Salih Hassan; Kiyoung Yoon; Sangtae Shin; Jongki Cho (Journal of Animal Reproduction and Biotechnology, 2015)
In the last 10 years, porcine somatic cell nuclear transfer to generate transgenic pig has been performed tremendous development with introduction and knockout of many genes. However, efficiency of porcine somatic cell nuclear transfer is still low and embryo transfer (ET) is one of important step for production efficiency. In porcine ET for production of transgenic cloned pig, we can consider many of points to increase production rates. In respect of seasonality and weather, porcine ET usually is not performed in summer and winter. Cloned transgenic embryos must be transferred into reproductive tracts of recipients where embryos are located after natural fertilization with similar estrous cycle. If cloned embryos with 2∼4 cell stage are transferred, they must be transferred into oviducts in periovulatory stage. Number and deposition sites of transferred cloned embryos are important. And we must compare the methods of ET between surgical and non-surgical ones in respect of production efficiency. Sow recipients after natural estrus is most preferred recipients however its cost is must be considered. Here we will review many of current studies about porcine embryo transfer to increase production efficiency of transgenic pigs and strategies for further studies.